Synergistic increase in cardiovascular risk in diabetes mellitus with nonalcoholic fatty liver disease: a meta-analysis. Issue 6 (June 2018) - Zhou, Yao-Yao; Zhou, Xiao-Dong; Wu, Sheng-Jie; Hu, Xian-Qing; Tang, Biao; Poucke, Sven van; Pan, Xiao-Yan; Wu, Wen-Jun; Gu, Xue-Mei; Fu, Shen-Wen; Zheng, Ming-Hua
Abstract : Background: Nonalcoholic fatty liver disease (NAFLD) has been linked to an increased risk of cardiovascular disease (CVD). To explore the impact of diabetes mellitus (DM) as a cardiovascular risk factor, this meta-analysis quantitatively assessed the association of NAFLD and CVD in diabetic patients. Methods: PubMed, EMBASE, and the Cochrane Library database were analyzed until the end of March 2017. Original studies analyzing the association between NAFLD and cardiovascular risk factors in the diabetic population were included. The available data related to outcome were extracted for the effect estimate using a random-effects model. The quality of the included studies was assessed using the Newcastle–Ottawa Quality Assessment Scale. Results: Of the 770 initially identified studies, 11 studies involving 8346 patients were finally included. The Newcastle–Ottawa Quality Assessment Scale scores suggested that the studies included were of high quality. The pooled effects estimate showed that diabetic patients with NAFLD showed a two times increased risk for CVD compared with patients without NAFLD (odds ratio=2.20, 95% confidence interval: 1.67–2.90). Subgroup analysis also yielded a markedly increased risk, with odds ratio (95% confidence interval) values of 2.28 (1.61–3.23) and 1.90 (1.48–2.45) in cross-sectional and cohort studies, respectively. Conclusion: This is the first meta-analysis investigating the relationship between NAFLD and CVD independent of the impact of DM. Our findings suggested that NAFLD increases the risk of CVD in populations with comparable DM profiles. Diabetic patients diagnosed with NAFLD might benefit from a more early cardiovascular risk assessment, thereby reducing CVD morbidity and mortality.